Creating Markets in Nepal : Country Private Sector Diagnostic - International Finance Corporation (International Finance Corporation, Washington, DC, 2018)
The purpose of this Country Private Sector Diagnostic (CPSD) is to assess opportunities and constraints holding back private sector growth. It conducts a diagnostic of the main cross-cutting constraints to private sector competitiveness and growth through data analysis, synthesis of existing research and stakeholder consultations. This exercise also identifies sectors that could play a key role in enabling Nepal’s growth, by either enabling other sectors or capitalizing on Nepal’s inherent comparative advantage to tap global markets. Sector deep dives help identify private sector constraints specific to these sectors, including sector-specific manifestations of cross-cutting constraints. The CPSD analysis finally identifies key recommendations on policy reforms and investments in public goods (including public-private partnerships) that could enable growth of a competitive private sector.